THE INFLUENCE OF GEOMORPHOLOGY TO LANGUAGE VARIATION IN THE WESTERN PART OF JAVA, INDONESIA - -, Evi Haerani; -, Dicky Muslim (Bulletin of Scientific Contribution, 2008)
In Indonesia, the western part of Java Island is known as a place with very diverse culture. There are 3 provinces in this region, namely West Java, Banten, and Jakarta Capital Special Region with more than 40 million populations. Sundanese is a main culture within this region, where focal area is around Bandung City. It is accompanied by 3 other subcultures, i.e. Cirebonese (around Cirebon City), Betawinese (Jakarta City and surrounding) and Bantenese (around Serang City).Geomorphological configuration of the study area is characterized by mountainous to coastal plain areas. It implies to the characteristic diversity of culture for every community including the development of local languages. This paper is aimed to map the relationship of local languages diversity (dialect) with their geomorphological conditions in the study area.Result of the study shows that Sundanese people commonly speak humble in polite manner and live on mountainous to hilly area. The Cirebonese speaks rather Javanese combined with impolite Sundanese and lives on the northern Java coastal plain as transition area between Sundanese and Javanese. Betawinese speak rather impolite and live on the coastal plain around Gulf of Jakarta. Bantenese speak rather impolite and live on coastal plain to gentle hilly area. This result suggests that there is relationship between the characteristics of utterances of people with the nature they live on.